IDENTIFICATION AND PATHOGENICITY OF ISOLATE OF BACTERIUM CAUSED LEAF BLIGHT DISEASE ON Maranta arundinacea - Supriadi Supriadi; Nildar Ibrahim; N. Karyani (Indonesian Agency for Agricultural Research and Development, 2000)
Arrowroot (Maranta arundinacea L) is a multi-functional plant used as a source of medicinal, carbohydrate (especially the green leaf type) and also as ornamental plant (the streaked white leaf type). A leaf blight disease is recently found on the streaked white type in Bogor. Preliminary observation indicated that the disease was associated with bacterial infection. The cause of the disease has not been studied. This study was aimed to identify the cause of bacterial leaf blight disease. Experiments were conducted in the laboratory of Research Institute for Spice and Medicinal Crops in Bogor. Suspected bacteria were isolated from diseased leaves. The results showed that the bacterium produced white to brownish colonies on rich agar media containing peptone or cassamino acid. 3-5 mm in diameter, circular, and did not yield fluorescent pigment on King’s B medium. The bacterium formed rod cells, Gram negative, accumulated poly β hydroxybutyrate, utilized glucose under aerobic condition, not hydrolyse arginine and starch, positive catalase, insensitive to tetrazolium salt (0.1%), and grew at 35oC. The bacterium neither producted xanthomonadin pigment nor reduced nitrate to nitrite. The pathogen was tolerant to penicillin and oxolinic acid, but sensitive to streptomycin and oxytetracycline at high concentration (1.000 ppm). These characteristics met to those of Pseudomonas cepacia. Pathogenicity test on detached leaves showed that the typical symptom of blight was similar to that of natural infection on arrowroot. This is the first report on occurrence of P cepacia on arrowroot plant.